A Systematic Review of Young Learners™ Second Language Acquisition in the Indonesian Context - Silvy Kusumawardani, Julian; Ginanjar Anjaniputra, Agung (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2024)
This study reports on how the studies concerning second language acquisition (SLA) in Indonesia have been conducted in association to the teaching and learning activities of young language learners and to what extent the studies contribute to the development of SLA in Indonesia. Language acquisition (LA) is related to the way individuals acquire the target language for its words, structures, meaning, pragmatics and so forth. However, previous research reviewing young EFL learners™ language acquisition in the Indonesian EFL context is still limited. Therefore, a total of 40 selected papers was reviewed to find out the current state of SLA in Indonesian. According to the outcome of the review, SLA in the Indonesian context has been investigated regarding the beginning processes of TEYL, the teaching-learning strategies, the teaching media, the teaching methods, young learners' language developments, the advantages and disadvantages of learning English. The present paper presents possible suggestions for English teachers, school administrators, and parents to be involved in teaching and learning English for young learners in the Indonesian context.